Sistem Pendukung Keputusan Manajemen Pemilihan Aplikasi Jasa Transportasi Online Menerapkan Metode ROC dan WASPAS - Marsono, Marsono; Sudarmanto, Sudarmanto; Wasiati, Hera; Nasyuha, Asyahri Hadi (Forum Kerjasama Pendidikan Tinggi, 2023)
Transportation in Indonesia has various types of vehicles, ranging from two-wheeled to six-wheeled, which are adjusted according to user needs. The ease of ordering transportation services is also increasing with the application that can be downloaded on a smartphone. This application provides convenience and security, as well as setting tariff rates according to the intended destination. Even though using an online transportation service ordering application has many advantages, such as convenience and security, there are some drawbacks that users often face. One of them is the discrepancy between the travel time stated in the application and reality, which can result in delays if there is an urgent need. In addition, sometimes the application also provides a longer travel route even though there is a road that is closer to the destination, so the driver must use an alternative road outside the specified route. Therefore, evaluation of the applications used needs to be done by comparing one application with another. This study aims to use a Decision Support System (SPK) to assist online transportation users in choosing the best application, taking into account factors such as the accuracy of travel time and the efficiency of the route taken by the application. There are many DSS methods that can be applied in the process of selecting or selecting the object under study, in this study the method used is the ROC method as a weighting of the level of importance of each criterion and the WASPAS method for the ranking process for each alternative. The final result obtained is that the Grab application (A3) is declared the best application in online transportation services with an acquisition value of 0.9331Decision Support System